Serum cholesterol loading capacity on macrophages is linked to coronary atherosclerosis and cardiovascular event risk in rheumatoid arthritis. Issue 2 (16th September 2022) - Karpouzas, George Athanasios; Papotti, Bianca; Ormseth, Sarah; Palumbo, Marcella; Hernandez, Elizabeth; Adorni, Maria Pia; Zimetti, Francesca; Budoff, Matthew; Ronda, Nicoletta
Abstract : Objectives: Cholesterol loading capacity (CLC) describes the ability of serum to deliver cholesterol to cells. It is linked to foam cell formation, a pivotal step in atherosclerotic plaque development. We evaluate the associations of CLC with coronary atherosclerosis presence, burden and cardiovascular risk in patients with rheumatoid arthritis (RA). Methods: Coronary atherosclerosis (any, high-risk low-attenuation plaque and obstructive plaque) was evaluated with CT angiography in 141 patients. Participants were prospectively followed for 6.0±2.4 years and cardiovascular events including cardiac death, myocardial infarction, unstable angina, stroke, claudication, revascularisation and hospitalised heart failure were recorded. CLC was quantified as intracellular cholesterol in human macrophages after incubation with patient serum. Results: CLC was not linked to overall plaque presence or burden after adjustments for atherosclerotic cardiovascular disease (ASCVD) score, statin use and low-density lipoprotein cholesterol. However, CLC associated with presence and numbers of any, low-attenuation and obstructive plaques exclusively in biologic disease-modifying antirheumatic drugs (bDMARD) non-users (p for interaction ≤0.018). CLC associated with cardiovascular event risk overall after adjustments for ASCVD and number of segments with plaque (HR=1.76 (95% CI 1.16 to 2.67) per 1 SD increase in CLC, p=0.008). Additionally, bDMARD use modified the impact of CLC on event risk; CLC associated with events in bDMARD non-users (HR=2.52 (95% CI 1.36 to 4.65) per 1SD increase in CLC, p=0.003) but not users. Conclusion: CLC was linked to long-term cardiovascular event risk in RA and associated with high-risk low attenuation and obstructive coronary plaque presence and burden in bDMARD non-users. Its prospective validation as a predictive biomarker may be, therefore, warranted.